Tandem Mass Spectrometric Analysis and Cross-Species Comparison of Triacylglycerol Regioisomers in Mammalian Milk - Zhao, Qizhu; Fabritius, Mikael; Kalpio, Marika; Al Sazzad; Md Abdullah; Yang, Baoru (American Chemical Society (ACS), 2026)
Milk fats have complex profiles of triacylglycerols (TG) with a significant gap in understanding the species-specific compositions of regioisomers. This study comprehensively analyzed TG regioisomers in milk of eight mammalian species using ultra-high performance liquid chromatography-electrospray ionization tandem mass spectrometry and a calculation algorithm. Distinct TG regioisomer profiles were observed across species, shaped by the phylogenetic status and the structure of digestive tracts (ruminants, pseudo-ruminants, and non-ruminants). The ruminants (cow, goat, and sheep) exhibited highly similar milk TG regioisomeric profiles, while the pseudo-ruminant (camel) showed similar profiles to those of the non-ruminants (dog, horse, human, and pig). The non-ruminants showed a sn-2 abundance of palmitic acid in milk TGs; especially dog and pig milk displayed TG regioisomer profiles close to that of human milk. These findings provide novel insights into cross-species variation in lipid metabolism and the nutritional properties of milk fats, supporting product development for food and early life nutrition.